Performatywność baz danych na przykładzie bazy danych wizualnych „Niewidzialne miasto” - Krajewski , Marek (Człowiek i Społeczeństwo, 2013)
Databases are a form of social performance. This means that their creation is, as Jon McKenzie says, a challenge to the social order – an attempt to stop the changes or to run them. Databases are constructed mainly in order to cognitively and technically control a fragment of reality, to increase the effectiveness of our actions. Thus, although the database seems to be something sedate, dead set of information, its essence lies in the startup of human action, and thus on the transformation of the existing order. This starts with the collection of information and their transformation into the data, with correlation them with each other, seeking within them patterns and trends and in the end, using knowledge for transformation of reality. At each stage of constructing the database we encounter so performance – action that expresses a claim to change reality and that results in starting the activity of individuals, stimulation of various forces. This look at the database promotes their defetishisation as hard reference point for our activity – they are at every stage the effect of overlapping of performative actions.